2020
DOI: 10.18388/abp.2020_2871
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine-mediated cardiotoxicity is associated with altered energy metabolism in isolated rat hearts

Abstract: Olanzapine is an antipsychotic drug routinely used for the treatment of schizophrenia. Although the olanzapine treatment is associated with disturbed electrical heart activity, the exact mechanism underlying this severe adverse effect remains unclear. Recently, olanzapine administration was demonstrated to be associated with elevation of blood glucose and lower levels of free fatty acids. Therefore, we investigated the effect of acute olanzapine administration on pathways regulating the cardiac energy metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…The use of captopril, an angiotensin-converting enzyme inhibitor, significantly protected against the above clozapine-induced effects in rats[ 103 ]. In a rat model, olanzapine-induced cardiotoxicity was reported to be associated with increased acetyl-CoA carboxylase phosphorylation and tissue ATP levels and lower phosphorylation levels of Akt and its downstream product AS160[ 104 ]. These generally descriptive studies reinforced the mitochondria-involved mechanisms and implied that inflammatory cell death might be critically involved in antipsychotic cardiotoxicity.…”
Section: Mechanisms Underlying Antipsychotics Cardiotoxicitymentioning
confidence: 99%
“…The use of captopril, an angiotensin-converting enzyme inhibitor, significantly protected against the above clozapine-induced effects in rats[ 103 ]. In a rat model, olanzapine-induced cardiotoxicity was reported to be associated with increased acetyl-CoA carboxylase phosphorylation and tissue ATP levels and lower phosphorylation levels of Akt and its downstream product AS160[ 104 ]. These generally descriptive studies reinforced the mitochondria-involved mechanisms and implied that inflammatory cell death might be critically involved in antipsychotic cardiotoxicity.…”
Section: Mechanisms Underlying Antipsychotics Cardiotoxicitymentioning
confidence: 99%
“…A study based on zebrafish embryos has shown that, clozapine can increase the levels of reactive oxygen species and a lipid peroxidation marker leading to oxidative and inflammation, thus resulting in cardiotoxicity ( 8 ). Another study based on male rats showed that, in the rat heart, olanzapine can increase the level of acetyl-CoA carboxylase phosphorylation and tissue ATP level, also reduce the level of Akt and its downstream products AS160, which may be involved with the mechanism for the adverse cardiac effects ( 9 ). Data from a Italian study showed that the elderly frail subjects were more likely to be prescribed second-generation antipsychotics and this may be involved in cardiometabolic disorders and other comorbidities ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patrik Gulac e colaboradores (2020), relata que a incidência de morte súbita cardíaca em pacientes tratados com olanzapina é duas vezes maior do que em não usuários, mas o mecanismo subjacente aos efeitos cardíacos adversos graves permanece pouco compreendido (BEAUCHEMIN; GEGUCHADZE; GUNTUR; NEVOLA et al, 2020;GULAC;ARNOLD;GRMAN;CARREL et al, 2020). Fonte: Próprio autor.…”
Section: Lista De Figurasunclassified